(untitled) (Journal of the College of Basic Education, 2026)
This research deals with the subject of educational linguistics as one of important branches of linguistics in field of language teaching and learning methods, because it focuses on the study of language in the context of teaching and learning, in addition to its interest in how language is acquired, taught, or learned. It combines linguistic and psycolinguistics in order to understand how to improve language teaching and learning processes, and promoting effective communication in different educational contexts. The nature of the research was required to be divided into three sections, that deals with the definition of linguistics in terms of the relationship between educational linguistics and applied linguistics and the concept of each. In addition to explaining the methods, tasks, and principles of linguistics.